2018
DOI: 10.1155/2018/6930986
|View full text |Cite
|
Sign up to set email alerts
|

Solitary CNS Metastasis on Initial Presentation of High Grade Serous Carcinoma of the Fallopian Tube

Abstract: A 68-year-old woman presented with a three-week history of confusion and anomic aphasia. Imaging of her head demonstrated a single large left frontal mass. Pathology revealed metastatic adenocarcinoma of Müllerian origin. Subsequent surgery revealed a small primary site in a fallopian tube, high left para-aortic lymphadenopathy, and no disseminated intraperitoneal disease. This case was remarkable in that CNS metastasis was her presenting symptom and was restricted to a solitary brain lesion, and other disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…1,5,6 In the present study, we found that there were no pediatric or ado- Clinicians have observed atypical and varied symptoms of PFTC. 14 In this study, only 7.02% (4/57) of patients experienced typical Latzko's triad symptoms. Those at advanced stages always presented with abdominal pain and distension.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…1,5,6 In the present study, we found that there were no pediatric or ado- Clinicians have observed atypical and varied symptoms of PFTC. 14 In this study, only 7.02% (4/57) of patients experienced typical Latzko's triad symptoms. Those at advanced stages always presented with abdominal pain and distension.…”
Section: Discussionmentioning
confidence: 49%
“…Clinicians have observed atypical and varied symptoms of PFTC 14 . In this study, only 7.02% (4/57) of patients experienced typical Latzko's triad symptoms.…”
Section: Discussionmentioning
confidence: 51%
“…A 50-year-old woman with metastasis of a fallopian tube cancer to the ovary has also been reported [15]. Other uncommon metastatic regions, including the central nervous system (CNS), uterus and diaphragm, have also been reported recently [11,21,32]. The reported metastatic regions of PFTC are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis of this disease has been reported in recent years. The rare and distant metastasis sites of PFTC include supradiaphragmatic lymph nodes, axillary lymph nodes, brain, vagina, femur and rib, ovary, cervix, lung, spine, colon, skin and diaphragm [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. However, to our knowledge, no mediastinal metastasis of this tumor has been reported yet.…”
Section: Discussionmentioning
confidence: 99%